2013
DOI: 10.1002/ptr.5014
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of a Lecithinized Delivery System of Curcumin (Meriva®) to Alleviate the Adverse Effects of Cancer Treatment

Abstract: A proprietary lecithin delivery system of curcumin (Meriva) was evaluated in a controlled study to assess its efficacy in alleviating the side effects of cancer chemo-and radiotherapy in 160 patients undergoing these treatments. In both cases, a semi-quantitative evaluation of the side effects was carried out using a visual analogue scale, assessing also the plasma free radical status in all patients. Results showed that lecithinized curcumin might alleviate the burden of side effects associated to chemo-and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 23 publications
0
82
0
1
Order By: Relevance
“…Previous reports show that at low dose, curcumin repaired and regenerated liver tissues by redeveloping liver microvascular in diabetic rats. Clinical trials using Meriva®, a lecithinized formulation of curcumin (Belcaro et al, ), had beneficial effects on microcirculation and edema in diabetic microangiopathy and retinopathy (Belcaro et al, ). Curcumin is a cheap nutritional ingredient with negligible side effects at low doses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that at low dose, curcumin repaired and regenerated liver tissues by redeveloping liver microvascular in diabetic rats. Clinical trials using Meriva®, a lecithinized formulation of curcumin (Belcaro et al, ), had beneficial effects on microcirculation and edema in diabetic microangiopathy and retinopathy (Belcaro et al, ). Curcumin is a cheap nutritional ingredient with negligible side effects at low doses.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding these biochemical improvements, the efficacy of curcuminoids in reducing clinical outcomes has been controversial. Belcaro et al (2013) reported a significant effect of 4-month treatment with Meriva ® in improving QoL and reducing the burden side effects associated with chemotherapy or radiotherapy in 160 cancer patients. Combination therapy with curcuminoids (480 mg) and quercetin (20 mg) for 6 months was reported to reduce both the size and number of colorectal polyps in a small study in five patients with familial adenomatous polyposis (Cruz-Correa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, a powerful promoter of anti-oxidant response [16], is one of the best investigated natural products [17], and is now commercially available in a lecithin delivery system (Meriva®, Indena SpA, Milan) that improves curcuminoids bio-availability. This formulation has accumulated significant clinical documentation of efficacy in various conditions triggered and/or sustained by chronic inflammation, like diabetic microangiopathy and retinopathy [18], central serous chorioretinopathy [19], benign prostatic hyperplasia [20], chemotherapy-related adverse effects in cancer patients [21] and osteoarthritis [22]. In addition, curcumin as Meriva® was also recently validated as an analgesic agent with potency at least comparable to that of acetaminophen [23].…”
Section: Introductionmentioning
confidence: 99%